Audiovisual Translation in the Age of Netflix: How “Netflixication” Has Impacted Translation Practices and the Viewing Experience - Moreau, Eponine (Journal of Audiovisual Translation, 2025)
This paper examines Netflix’s most prominent transnational strategies and their impact on the AVT sector in general, and the work of subtitlers in particular. After a brief historical overview of the milestones that have led Netflix to become the most influential streaming platform, this paper explains how the company’s main strategies and practices, namely its release model and its self-produced originals, may impact the work of AV practitioners and the quality of the subtitles. It then explores the apparent paradox pertaining to Netflix’s localization practices, which seemingly serve its purpose of local integration – by allowing viewers to watch audiovisual content subtitled in their own language – while also conflicting with established national subtitling practices. More specifically, the discussion focuses on using the same template as a starting point to produce subtitles in multiple languages and Netflix Timed Text Style Guides. Lay summary This paper examines Netflix’s most prominent transnational strategies and their effects on the audiovisual translation sector in general, and the work of subtitlers in particular. After a brief historical overview of the milestones that have led Netflix to become the most influential streaming platform, the article explains how the company’s main strategies and practices, namely its release model, its self-produced originals and, more recently, its integration of AI and machine-translation tools, may impact the work of audiovisual practitioners and the quality of subtitles. It then explores the apparent paradox pertaining to Netflix’s localization practices, which seemingly serve its purpose of local integration – by allowing viewers to watch audiovisual content subtitled in their own language – while also conflicting with established national subtitling practices. More specifically, the discussion focuses on using the same template as a starting point to produce subtitles in multiple languages and on Netflix Timed Text Style Guides. The paper concludes by considering the implications of Netflix’s transnational strategies for subtitling norms and by outlining avenues for future research.